THE ROLE OF HUMAN RESOURCE MANAGEMENT IN IMPROVING EMPLOYEE PERFORMANCE IN PRIVATE COMPANIES - Eddy Hermawan Hasudunga Panjaitan; Reni Rupianti; Tekat Sukomardojo; An Ras Try Astuti; Agus Sutardjo (Komitmen: Jurnal Ilmiah Manajemen, 2023)
A company needs employees with good performance. Through this good performance, the company can compete and develop into a bigger company. There are various strategies to improve employee performance, one of which is human resource management. This study aims to see the role of human resource management in enhancing employee performance in private companies. This research will be carried out using a descriptive qualitative approach. The data used in this study comes from various research results and previous studies, which still have relevance to the contents of this research. This study then found a positive influence of human resource management on improving employee performance in private companies. This is due to the fact that human resource management requires three essential roles: the administrative role, the operational role, and the strategic role. Humans are the source of all the company's problems, hence these three positions are vital to its management.